Makna Life Goals dalam Film Rentang Kisah: Analisis Naratif Model Tzvetan Todorov - Devi Putri Aji; Kamila Adnani (UIN Raden Mas Said Surakarta, 2023)
The Rentang Kisah film is adapted from a best-selling novel which outlines the life journey of a Gita Savitri Devi. The purpose of this study is to describe the meaning of Life Goals in the film of Rentang Kisah through the analysis of Tzvetan Todorov's model. In this study, two problems were found, namely: first, how is the storyline of the film of Rentang Kisah examined through Tzevetan Todorov's analytical knife; and second, how the meaning of life goals in the film of Rentang Kisah is described in Tzvetan Todorov's narrative analysis. This researcher found several data findings that the storyline of the film of Rentang Kisah is depicted through 3 narrative lines in terms of the analysis of Tzvetan Todorov's model. There are 7 meanings of life goals found in the film texts studied, which include 4 meanings of life goals in the middle plot, and 3 meanings of life goals in the final plot. However, there is no life goals meaning in the beginning plot of the film.